2006
DOI: 10.1207/s15327590ijhc2003_4
|View full text |Cite
|
Sign up to set email alerts
|

Presenting a Submenu Window for Menu Search on a Cellular Phone

Abstract: This study proposes a submenu window as a navigation aid for mobile Internet access on a cellular phone. The submenu window presents child-level menu items along with their upper-level menu. The effectiveness of the submenu window was investigated in an experiment. The factors manipulated in the experiment include the types of submenu window, age of participants, and timing of presenting the submenu. Task completion time, number of button clicks, and subjective preference were measured while the participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…In this paper we only focused on the static menu as the target; adaptive/dynamic menu (e.g., [2,3,7]) that changes menu contents in adapting to varying usage is a future target.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we only focused on the static menu as the target; adaptive/dynamic menu (e.g., [2,3,7]) that changes menu contents in adapting to varying usage is a future target.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…The performance of the menu, i.e., the average selection time of menu items, depends on many factors, including its structure, layout, and colors. There have been many studies on novel menus (e.g., [2,3,7]), but there has been little Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page. To copy otherwise, to republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee.…”
Section: Introductionmentioning
confidence: 99%
“…Individual differences, especially expertise effect, existed in computers, and a user's mental model had an effect on performance on menus in cell phones (Hollands & Merikle, 1987;Ziefle & Bay, 2004). Help fields were shown to improve performance as well (Beck et al, 2006;Jacko et al, 2005;Lee et al, 1986).…”
Section: D Menu Design Comparisonmentioning
confidence: 98%
“…According Downloaded by [UQ Library] at 04:39 20 June 2015 to the studies conducted by several researchers, navigation aids such as feedback, visual momentum, and a map of the menu structure promotes learning of the user interface and improves performance (Han & Kwahk, 1994;Tang, 2001). Furthermore, Beck, Han, and Park (2006) concluded that submenu windows could reduce trial and error and improve user satisfaction when presented properly, and the separate submenu windows with no delay were recommended. But in real situations, a submenu with no display is hard to implement because all information including child-level items should be called up whenever their upper-level menu is shown.…”
Section: Help Fieldsmentioning
confidence: 99%
“…The performance of the menu depends on many factors: structure, layout, colors and so on. There has been many studies on novel menus (e.g., [2,3,8]), but there has been little work on improving the performance of a menu by changing its structure [1,6,11]. There have been many studies on menu-design and menulayout from the standpoint of the user interface.…”
Section: Introductionmentioning
confidence: 99%